Wajah Politik Muhammadiyah - Mubarak, Adil (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2012)
Muhammadiyah is known as community organization based on religious principle which act on disseminating Islamic values in order to reform Islamic principle to become purely. In its growth, Muhammadiyah does not far away from political activities that is not really its field. Various roles in political context are played by Muhammadiyah both external an internal space. This article’s aim is describing relationship pattern between Muhammadiyah and political field to reinforce Muhammadiyah actual face in politic. Keywords : Muhammadiyah, politic, community organization